Uncovering the factors of financial well-being: the role of self-control, self-efficacy, and financial hardship - Jorge Hernandez-Perez; Salvador Cruz Rambaud (Future Business Journal)
Abstract Financial well-being, a key determinant of life satisfaction, is increasingly threatened by economic volatility and complex financial systems. This study examines the interplay between psychological traits—financial self-control and financial self-efficacy—and their relationship with financial well-being, mediated by financial hardship. Theoretical frameworks include Scheier and Carver’s Self-Regulation Theory (In: Affect and cognition. Psychology Press, Philadelphia, pp 157–183, 2014), the Behavioral Life-Cycle Hypothesis (Shefrin and Thaler in Econ Inq 26:609–643. 10.1111/j.1465-7295.1988.tb01520.x, 1988; Thaler in Am Econ Rev 108:1265–1287, 2018), and Bandura’s Self-Efficacy Theory (in, Self-efficacy in changing societies, Cambridge University Press, Cambridge, 1997). Data were drawn from the Spanish Survey of Financial Literacy, a nationally representative sample of 8554 individuals. Spain’s unique macroeconomic context, influenced by the 2008 financial crisis and cultural factors such as family financial interdependence, provides a compelling backdrop for analysis. To test the hypotheses concerning the direct and indirect relationships between self-regulation factors and financial well-being, partial least squares structural equation modeling (PLS-SEM) was employed. The findings reveal a robust negative association between deficiencies in financial self-control (β =  − 0.250, p < 0.001) and financial self-efficacy (β =  − 0.265, p < 0.001) and a corresponding decline in financial well-being. Furthermore, financial hardship exhibits a robust negative correlation with financial well-being (β =  − 0.410, p < 0.001) and partially mediates the relationships between self-regulation factors and financial outcomes. Specifically, financial hardship accounts for 41% of the total effect of financial self-control on financial well-being and 23% of the effect of financial self-efficacy. These findings underscore the pivotal role of psychological traits in shaping financial outcomes and highlight financial hardship as a critical mechanism for improving financial well-being. This study contributes to the extant literature by integrating financial hardship as a mediator and leveraging a unique dataset. It offers actionable insights for policymakers and financial institutions to design interventions promoting financial resilience. Specifically, the integration of automated savings programs and behavioral nudges has been demonstrated to enhance financial self-control, while financial education workshops have been shown to improve financial self-efficacy. Addressing financial hardship through policies such as debt relief and subsidized counseling can mitigate the adverse effects of financial stress. By elucidating the pathways linking self-regulation to financial well-being, this research deepens our understanding of the cognitive, emotional, and behavioral drivers of financial decision-making, with implications for theory and practice. Finally, these findings can inform targeted interventions addressing specific financial challenges, fostering greater financial resilience and stability.